2011
DOI: 10.1039/c0pp00381f
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy and two-photon bio-imaging applications of hydrophobic chromophores through amphiphilic polymer delivery

Abstract: The synthesis and photophysical properties of two lipophilic quadrupolar chromophores featuring anthracenyl (1) or dibromobenzene (2) were described. These two chromophores combined significant two-photon absorption cross-sections with high fluorescence quantum yield for 1 and improved singlet oxygen generation efficiency for 2, in organic solvents. The use of Pluronic nanoparticles allowed a simple and straightforward introduction of these lipophilic chromophores into biological cell media. Their internal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…Four years later another group demonstrated that singlet oxygen was efficiently generated by excitation of 4-(diphenylaminostilbene)-substituted porphyrin-based PSs molecularly designed for enhanced two-photon absorption at 780 nm (within the "tissue window") using a 150 femtosecond pulsed laser [50]. The development of other 2P-PDT agents such as lipophilic quadrupolar chromophores carrying anthracenyl and dibromobenzene residues [103] and hydrophilic conjugated porphyrin dimers [104,105] with realistic and practical 2PA cross-sections having at least >100 GM (e.g. 8,000 -17,000 GM for the porphyrin dimers), good photostability and high light absorptivity within the "tissue window" have also been reported.…”
Section: Two-photon Pdt (2p-pdt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Four years later another group demonstrated that singlet oxygen was efficiently generated by excitation of 4-(diphenylaminostilbene)-substituted porphyrin-based PSs molecularly designed for enhanced two-photon absorption at 780 nm (within the "tissue window") using a 150 femtosecond pulsed laser [50]. The development of other 2P-PDT agents such as lipophilic quadrupolar chromophores carrying anthracenyl and dibromobenzene residues [103] and hydrophilic conjugated porphyrin dimers [104,105] with realistic and practical 2PA cross-sections having at least >100 GM (e.g. 8,000 -17,000 GM for the porphyrin dimers), good photostability and high light absorptivity within the "tissue window" have also been reported.…”
Section: Two-photon Pdt (2p-pdt)mentioning
confidence: 99%
“…The quadrupolar chromophores demonstrated effective cell killing upon 2PE at 820 nm and the conjugated porphyrin dimers were shown to be suitable for 2P-PDT in in vivo AMD models [103][104][105]. Dahlstedt et al (2009) investigated the effects of 2P-PDT using a range of conjugated porphyrin dimers with high two-photon absorption cross sections up to 17,000 GM.…”
Section: Two-photon Pdt (2p-pdt)mentioning
confidence: 99%
“…Pluronics (poloxamers) are commercially available watersoluble triblock copolymers of poly(ethylene oxide) and poly(propylene oxide) (PEO-PPO-PEO) and have been frequently used as a solubilization agent in drug formulations. Gallavardin et al [105] used the pluronic nanoparticles for encapsulating two-photon chromophores. Chowdhary et al [106] compared the pluronic P123 formulation with a lipidbased system to improve the verteporfi n delivery to lipoproteins in tumor and arthritis mouse models.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…One major issue when using fluorescent dyes is their loss of fluorescence intensity within a certain period of irradiation [98,99] (e.g. bleaching effect).…”
Section: Fluorescent Studiesmentioning
confidence: 99%